PENGARUH WFH, KOMUNIKASI KERJA DAN BUDAYA ORGANISASI TERHADAP PRESTASI KERJA PNS - Fithrotun Walidatun Sholihah; Naning Kristiyana; Dwi Warni Wahyuningsih (Gapenas Publisher, 2022)
The purpose of this study was to determine the partial effect of WFH on employee performance, partial effect on employee performance, partial effect of organizational culture on employee performance, and the simultaneous effect of WFH, work communication and organizational culture on employee performance. The method used in this research is descriptive quantitative. The research population was all civil servants in the General Section of the Graha Krida Praja Office, Ponorogo Regency with a sample of 48 employees taken with the saturated sample technique. The analysis tool uses multiple linear regression analysis. The results showed that : 1) WFH had a significant positive effect on employee performance, which was shown positively with a t-count value of 3.507 > ttable 2.0153 and a significant value of 0.001 <0.05. 2) Work Communication has a significant positive effect on Employee Work Performance which is shown positively by the t-test value obtained by the t-count value of 7.817 > t table 2.0153 and a significant value of 0.000 <0.05. 3) Organizational Culture has a significant positive effect on Employee Work Performance which is shown to be positive with a t value of 4.438 > t table 2.0153 and a significant value of 0.000 < 0.05 and 4) WFH, Communication and Organizational Culture simultaneously affect the Work Performance of Civil Servants General Section of the Office of Graha Krida Praja, Ponorogo Regency